Priority gender equality : action plan 2008-2013 (UNESCO ParisFR, 2009)
Describes the actions UNESCO is taking between 2008 and 2013 through its programme sectors in education, the sciences, culture and communication and information, in order to ensure that UNESCO programmes and initiatives contribute fully and actively to the pursuit of women's empowerment and gender equality efforts.
Keywords: GENDER EQUALITY